Psychological factors as determinants of use and adjustment to assistive technology by students with hearing impairment in tertiary institutions in Oyo State, Nigeria (2015)
Students with hearing impairment find it difficult to use and adjust to assistive technologies due to some psychological factors. This in turn tends to have great influence on their academic performance and psycho-social interactions with people around them. Consequently, this study, therefore, investigated some psychological factors as determinants of the use and adjustment to assistive technology by students with hearing impairment in tertiary institutions in Oyo State, Nigeria. Descriptive survey research design was adopted for the study, as purposive sampling technique was used to select the sixty respondents from two tertiary institutions in Oyo state. This study raised and answered three research questions tested at 0.05 level of significance. Multiple regression and Pearson's Product Moment Correlation (PPMC) were used as statistical methods of data analysis. The findings of this study revealed a significant relationship among the psychological factors: personality (r-0.402, P<0.05); self-esteem (r=0.309, P<0.05); and locus of control (r=0.800, P<0.05) on the use and adjustment to assistive technologies by students with hearing impairment in tertiary institutions. The study also established joint influence of the independent variables on the dependent variables (F=34.662, P<0.05). The results yielded a coefficient of multiple regression which implies that the three independent variables jointly accounted for the use and adjustment to assistive technology by students with hearing impairment. Personality factor (β=0.707, t-5.173, P<0.05); self-esteem (β=0.664, t=2.310, P<0.05); and locus of control (β=0.751, t=8.502, P<0.05) had relative influence on the use and adjustment to assistive technology by students with hearing impairment. Assistive technologies are effective in boosting the performance of students with hearing impairment in tertiary institutions. Therefore, the psychological factors of students with hearing impairment should be enhanced before introducing assistive technology. Students should be taught how to develop the right attitude towards the use of assistive technologies.